Evaluation of the efficacy of a cannabidiol and cannabidiolic acid rich hemp extract for pain in dogs following a tibial plateau leveling osteotomy - Klatzkow, Sarah; Davis, Garrett; Shmalberg, Justin; Gallastegui, Aitor; Miscioscia, Erin; Tarricone, Jason; Elam, Lindsay; Johnson, Matthew D.; Leonard, Katelyn M.; Wakshlag, Joseph J. (Frontiers in Veterinary Science, 2023)
Objective To determine the impact of a cannabidiol (CBD) and cannabidiolic acid (CBDA) rich hemp product on acute post-operative pain in dogs following a tibial plateau leveling osteotomy (TPLO), and to evaluate for changes in early bone healing, serum chemistry profiles, and complete blood counts. Methods In this randomized, placebo controlled, blinded clinical trial, 44 client-owned dogs were assigned to receive either a CBD/CBDA product dosed at 2–2.5 mg/kg PO every 12 h or a placebo for 4 weeks following a TPLO. Variables evaluated before (week 0), and at 2 and 4 weeks post-operatively included standardized veterinary assessments for pain score, weight-bearing, and lameness, the Canine Brief Pain Inventory (pain interference score–PIS, pain severity score–PSS), and serum biochemistry. Complete blood counts were performed at weeks 0 and 4. Additionally, orthogonal radiographs evaluating the degree of healing were taken at week 4. A mixed model analysis, analyzing changes of variables of interest from enrollment baseline to all other time points was utilized, with a p-value ≤ 0.05 considered significant. Results Of the 44 enrolled patients, 3 were lost to follow up and excluded from analysis. No significant differences were noted between placebo (n = 19) and CBD/CBDA (n = 22) groups at any point in pain score, degree of lameness, degree of weight-bearing, PIS, PSS, or radiographic healing of the osteotomy. A significant finding of elevation of ALP above normal reference range in the treatment group was identified (p = 0.02) and eosinophil count was affected by treatment (p = 0.01), increasing from baseline in placebo and decreasing in treatment groups. Finally, a significant difference (p = 0.03) was noted at 2 weeks post-operatively where 4 patients in the placebo group and no treatment patients received trazodone to facilitate activity restrictions. Clinical significance Use of a CBD/CBDA rich hemp product dosed at 2–2.5 mg/kg PO every 12 h did not have a significant impact on pain or delay early bone healing. A statistically significant increase in ALP, decrease in eosinophils, and reduced use of trazodone was identified in the treatment group.